Ringen mit der Vergnangenheit: Versuch einer individuellen und kollektiven Aufarbeitung der Vergangenheit, besonders im Hinblick auf die Beziehung zwischen als inoffizielle Mitarbeiter angeworbenen kirchlichen Amtsträgern und der kommunistisch-sozialistischen Staatssicherheit - Joób, Máté (European Journal of Mental Health, 2013)
Wrestling with the past: An attempt at coming to terms with the past on individual and community level – with special consideration of the relationship between church informants and Communist-Socialist state security: The study describes the social context, in which the Evangelical Lutheran Church in Hungary made an attempt at coming to terms with the relationship between church informants and state security following the collapse of the communist system. It also gives an overview of the process of the formation and work of the church committee whose role was to disclose and analyse the relationship between state security services and certain church people. Furthermore, it examines statements given by church bodies and individuals in order to find some aspects that can answer the following question: why has the process of coming to terms with the past become unexpectedly difficult in the given church community and why has the generally formulated pattern of repentance – confession of sins – forgiveness proved to be inapplicable in settling the question in an adequate way.